2020
DOI: 10.2337/dc19-0760
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Glycemic Status and the Risk of Parkinson Disease: A Nationwide Population-Based Study

Abstract: Previous studies have suggested that diabetes increases the risk of Parkinson disease (PD); however, this has not been conclusively established. We analyzed the risk of PD based on baseline glucose tolerance status in a large-scale cohort representative of the general Korean population. RESEARCH DESIGN AND METHODS This analysis was performed in a cohort of 15,168,021 adults aged ‡40 years who underwent health checkups under the National Health Insurance Service between January 2009 and December 2010. The clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 35 publications
(47 reference statements)
2
55
0
Order By: Relevance
“…Our pooled analysis failed to demonstrate any significant association between GTZ use and the PD risk (HR, 0.88; 95% CI, 0.66 to 1.16; I 2 , 92%; p = 0.35) (Figure 4). On the sensitivity analysis, we found the study of Rhee et al (37) to exert an undue influence on the pooled effect size, and we found a statistically significant reduction in the PD risk after its exclusion (HR, 0.78; 95% CI, 0.65 to 0.93; I 2 , 59%; p = 0.05). There was no change in the significance of the results on the sequential exclusion of the remaining studies.…”
Section: Meta-analysismentioning
confidence: 66%
See 1 more Smart Citation
“…Our pooled analysis failed to demonstrate any significant association between GTZ use and the PD risk (HR, 0.88; 95% CI, 0.66 to 1.16; I 2 , 92%; p = 0.35) (Figure 4). On the sensitivity analysis, we found the study of Rhee et al (37) to exert an undue influence on the pooled effect size, and we found a statistically significant reduction in the PD risk after its exclusion (HR, 0.78; 95% CI, 0.65 to 0.93; I 2 , 59%; p = 0.05). There was no change in the significance of the results on the sequential exclusion of the remaining studies.…”
Section: Meta-analysismentioning
confidence: 66%
“…Twelve articles were excluded because 10 compared the PD risk between patients with and without DM and did not focus on specific DM medications (16-25) and 2 (26,27) had overlapping data with another one (28). Finally, 10 studies met the inclusion criteria and were analyzed for this review (28)(29)(30)(31)(32)(33)(34)(35)(36)(37). Table 1 presents characteristics of all included studies.…”
Section: Search Results and Details Of Included Studiesmentioning
confidence: 99%
“…Subjects were classified according to smoking status as nonsmoker, former smoker, or current smoker. Individuals who consumed 30 g of alcohol per day were classified as being heavy alcohol consumers [ 22 , 23 ]. Regular physical activity was defined as performance of strenuous exercise for at least once per week [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Metabolic diseases, such as diabetes and obesity, increase susceptibility for additional long-term complications, including Parkinson disease (PD). Rhee et al (1) aim to address this issue by using a large data set obtained from the Korean National Health Insurance consisting of a sample of over 15 million individuals aged 40 years and older who had undergone routine checkups between 2009 and 2010. They evaluated diabetes as a risk factor for PD by analyzing how PD risk varies according to baseline glucose tolerance status, diabetes duration, and comorbidities such as obesity, cardiovascular disease, and cerebrovascular disease.…”
mentioning
confidence: 99%